أثر طريقة التدريب الدائري على تعلم بعض المهارات القاعدية لدى لاعبي كرة القدم فئة أصاغر - يوسف قرميط; بافة عبد الله (My University, 2024)
تهدف الدراسة للتعرف على التدريب الدائري مفهومه وخصائصه وأهميته. وإبراز أهمية التدريب الدائري للاعبي كرة القدم بالنسبة لفئة أصاغر، وكذا التعريف بأهم المهارات القاعدية لكرة القدم التي يجب أن يتميز بها لاعب كرة القدم. كذلك تهدف للتعرف على دور التدريب الدائري في تطوير المهارات القاعدية )التسديد نحو المرمى بدقة، التمرير الطويل، المراوغة( للاعبي كرة القدم صنف أصاغر. ولهذا الغرض استخدمنا المنهج التجريبي للإجابة على الإشكالية المطروحة، وتكونت عينة الدراسة من ) 24 ( لاعب كرة قدم لفئة أصاغر تم اختيارها بشكل قصدي، ولجمع البيانات وتحليلها في الجانب الميداني تم الاعتماد على وضع ثلاثة برامج تدريبية )التسديد بدقة نحو المرمى، التمرير الطويل، المراوغة(، في نادي نجوم سيدي مخلوف بولاية الأغواط. وفي الأخير توصلنا الى أنه توجد فروق ذات دلالة إحصائية لاعتماد التدريب الدائري في تحسين كل من مهارة التسديد في المرمى، ومهارة التمرير الطويل، ومهارة المراوغة لدى لاعبي كرة القدم لصالح القياس البعدي.
دراسة تمت على مستوى اللاعبين الناشئين لكرة القدم في نادي نجوم سيدي مخلوف بولاية الأغواط
The study aims to identify circular training, its concept, characteristics and importance, Highlighting the importance of circular training for football players for younger groups, as well as introducing the most important basic football skills that a football player must excel at. It also aims to identify the role of circular training in developing basic skills (accurate shooting towards goal, long passing, dribbling) for junior football players. For this purpose, we used the experimental method to answer the problem raised, and the study sample consisted of (24) football players from a younger group that were chosen intentionally. To collect and analyze data on the field side, we relied on developing three training programs (accurate shooting at goal, long passing, and dribbling). At the Sidi Makhlouf Stars Club in Laghouat Province.Finally, we concluded that there are statistically significant differences in adopting circular training in improving the goal shooting skill, long passing skill, and dribbling skill among soccer players in favor of the post-measurement.